Current Strategies for Modulating Tumor-Associated Macrophages with Biomaterials in Hepatocellular Carcinoma - Qiaoyun Liu; Wei Huang; Wenjin Liang; Qifa Ye (Molecules, 2023)
Hepatocellular carcinoma (HCC) is the fourth most common cause of cancer-related deaths in the world. However, there are currently few clinical diagnosis and treatment options available, and there is an urgent need for novel effective approaches. More research is being undertaken on immune-associated cells in the microenvironment because they play a critical role in the initiation and development of HCC. Macrophages are specialized phagocytes and antigen-presenting cells (APCs) that not only directly phagocytose and eliminate tumor cells, but also present tumor-specific antigens to T cells and initiate anticancer adaptive immunity. However, the more abundant M2-phenotype tumor-associated macrophages (TAMs) at tumor sites promote tumor evasion of immune surveillance, accelerate tumor progression, and suppress tumor-specific T-cell immune responses. Despite the great success in modulating macrophages, there are still many challenges and obstacles. Biomaterials not only target macrophages, but also modulate macrophages to enhance tumor treatment. This review systematically summarizes the regulation of tumor-associated macrophages by biomaterials, which has implications for the immunotherapy of HCC.